THE IMPORTANCE OF THE MOTHER TONGUE AND READING LITERACY TEXTBOOK IN THE FORMATION OF STUDENTS' LINGUISTIC COMPETENCE (Academicia Globe: Inderscience Research, 2023)
In this article, students' learning of grammatical concepts as theoretical knowledge through "Mother language and reading literacy" classes, as well as the formation of linguistic competences in students, are considered.